2017
DOI: 10.1159/000480218
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA MEG3 Downregulation Triggers Human Pulmonary Artery Smooth Muscle Cell Proliferation and Migration via the p53 Signaling Pathway

Abstract: Background/Aims: Increasing evidence has demonstrated a significant role of long non-coding RNAs (lncRNAs) in diverse biological processes, and many of which are likely to have functional roles in vascular remodeling. However, their functions in pulmonary arterial hypertension (PAH) remain largely unknown. Pulmonary vascular remodeling is an important pathological feature of PAH, leading to increased vascular resistance and reduced compliance. Pulmonary artery smooth muscle cells (PASMCs) dysfunction is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 38 publications
2
83
1
1
Order By: Relevance
“…Current evidence has highlighted that lncRNA MEG3 was capable of targeting directly and activating p53 in various cell types . Consistent with these above reports, we identify that lncRNA MEG3 could directly bind to and regulate p53 expression in NMVMs by RIP and Western blot assays, but which were not entirely the same as Wu.et al research .…”
Section: Discussionsupporting
confidence: 91%
“…Current evidence has highlighted that lncRNA MEG3 was capable of targeting directly and activating p53 in various cell types . Consistent with these above reports, we identify that lncRNA MEG3 could directly bind to and regulate p53 expression in NMVMs by RIP and Western blot assays, but which were not entirely the same as Wu.et al research .…”
Section: Discussionsupporting
confidence: 91%
“…The pathogenesis of PAH is characterized by pulmonary vascular remodeling with stiffening of the elastic proximal pulmonary arteries and thickening of the intimal and/or medial layer of muscular arteries, resulting from aberrant PASMC proliferation, migration and apoptosis [4,43,44]. In this study, excessive proliferation and migration and apoptosis resistance were observed in the in vitro cultured PASMCs derived from MCT-treated rats.…”
Section: Discussionmentioning
confidence: 66%
“…Maternally expressed gene 3 (MEG3) is the first lncRNA that has been shown to function as a tumor suppressor and inhibit cell proliferation in numerous human cancer cell lines, and it is expressed in many normal human tissues [15][16][17]. Loss of MEG3 expression has been identified in many human tumors, including cervical cancer [18], retinoblastoma [19], ovarian carcinoma [20], gastric cancer [21], germ cell tumor [22], and squamous cell carcinoma [23], and such loss is indicative of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%